Remote control using telephone line / Mohd Zaid Zakaria and Mohamad Zuhairy Mohamed - Zakaria, Mohd Zaid; Mohamed, Mohamad Zuhairy (2005)
This system connected to the telephone line to control any switch in the home from the outside. However, it unable to control many switch in the same time. The circuits of this device construct using many main ICs. These ICs play the important role to receive the input and produce the output in logic system either 1 or 0 to transistor. The transistor act as the switch when receive high signal. Then the switch will be on and current from the source flow to the relay and the circuit will be in close loop. The circuit describe here can be used to switch up to 9 application .The digit 0 is used to toggle between the appliance mode and normal mode. Thus the telephone can use to switch ON or OFF the appliances also while being used for normal conversation. Once the switching operation is over, digit 0 is dialed again.